Effect of morphology and temperature treatment control on the photocatalytic and photoluminescence properties of SrWO4 crystals. Issue 2 (24th January 2020) - Dirany, Nadine; Hallaoui, Abdelali; Valmalette, Jean Christophe; Arab, Madjid
Abstract : This work reports the combined effect of the morphology and crystallization degree of the strontium tungstate (SrWO4 ) scheelite structure on its photocatalytic and photoluminescence properties. Abstract : This work reports the combined effect of the morphology and crystallization degree of the strontium tungstate (SrWO4 ) scheelite structure on its photocatalytic and photoluminescence properties. The difference in the precursor ratio leads to two morphologies, spindle and sphere, which remain unchanged with heat treatment up to 500 °C. However, the crystallite sizes of the as-obtained samples and samples treated at 300 and 500 °C are about 50–74 nm for spindles and 44–110 nm for spheres. Both morphologies and thermal treatments lead to the variation in the photoluminescence and photodegradation of rhodamine (RhB) and methylene blue (MB) dyes under UV irradiation. A stronger photodegradation efficiency was found for RhB (90%) than for MB (72%). The photoinduced mechanism is more significant for RhB and becomes more efficient for samples treated at high temperature, while the photocatalysis of MB is weak due to the adsorption process. A broad visible photoluminescence band was observed at room temperature and chromaticity coordinates were identified, which confirmed the emission wavelength. The most intense photoluminescence was obtained for samples treated at 300 °C, corresponding to the optimal disordered structures and accompanied by a redshift wavelength for both spheres and spindles. In this case, the spindles showed the most intense photoluminescence, almost ten times higher than that in spheres.